The importance of including ADHD in the differential diagnosis in adults. About a case - E. González Laynez; B. Gamo Bravo; S. M. Bañón González; N. Ogando Portilla (European Psychiatry, 2024)
Introduction ADHD is a diagnosis almost always made in childhood or adolescence and oftent difficult to make it new in adults because it is not thought of in the differential diagnosis process and for the lack of experience from adult devices.